Number of children and their education in Philippine households - Orbeta, Aniceto Jr (The Philippine Review of Economics, 2009)
This paper shows how large family size can be important contributor to poverty in the Philippines. It examines one of the mechanisms behind this link by focusing on the relation between the number of children and school attendance of children 6-24 years old. It surveys the international literature to establish how the problem has been approached and what the results are for other countries. It then formulates and tests a model using a nationally representative household survey data for the Philippines to explain what determines the decision to keep children in school. The model specifically considered the endogeneity of the number of children-in-school attendance equations.